A new method for estimating the EFV distillation curve - Tarifa, Enrique Eduardo (2009)
This work presents a new method to estimate the equilibrium flash vaporization (EFV) distillation curve from standard laboratory analytical assay procedures. In this method, experimental data are utilized by a chemical process simulator to obtain the EFV curve. Any simulator able to model petroleum can be used for this task. To evaluate the performance of the proposed method, several types of petroleum were analyzed experimentally in this work. The obtained curves were compared with those produced by other methods showing a good match. The main advantage of the proposed method is its non-dependence on experimental data.